RESPON TANAMAN PAKCOY (Brassica rapa L.) TERHADAP PEMBERIAN POC DAN PUPUK KOTORAN AYAM PADA TANAH GAMBUT PEDALAMAN - Susi Kresnatita; Wahyu Widyawati; Hadinnupan Panupesi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
This research was to discover the effect of giving Nasa POC and chicken manure fertilizer on the growth and yield of pakcoy in inland peat. The research used a Completely Randomized Factorial Design. Factor I: Nasa POC (0, 6, 12, and 18 ml POC L-1 water) and Factor II: Chicken Manure Fertilizer (0, 10, 20, and 30 t.ha-1). The research result revealed that there was an interaction between giving Nasa POC and chicken manure fertilizer on the variable of plant height growth aged 3 and 4 WAP, number of leaves aged 3 WAP, leaf area, and pakcoy yield components, such as total fresh weight of the plant and dry weight of the plant. The interaction between Nasa POC 12-18 ml L-1 water with chicken manure on dose 20-30 t.ha-1 revealed the highest growth and yield of pakcoy. The Nasa POC treatment genuinely affected the plant height, number of leaves, leaf area, and pakcoy plant yield components, such as the plant's total fresh and dry weight. Chicken manure had a very real effect on plant height, number of leaves, leaf area as well as total fresh weight of the plant and dry weight of the plant.